ANALISIS PERMASALAHAN SISWA YANG KESULITAN MEMBACA PADA KELAS I DI SEKOLAH DASAR - Sara M. Simangunsong; Andi Kilawati; Janes Jainurahma (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
The reading skill is a fundamental component of the grade I curriculum, yet numerous students continue to grapple with competencies such as letter recognition, syllable formation, and basic reading comprehension. The objective of this study is to examine the factors that contribute to reading difficulties experienced by students in the first grade of elementary school. The research method employed is a descriptive qualitative approach, which incorporates observation, interview, and documentation techniques. The findings indicate that the factors contributing to reading difficulties include insufficient early reading stimulation, unvaried learning methods, and the absence of parental involvement in their children's reading learning processes. Furthermore, the constraints imposed by learning media and the excess of students beyond the capacity of the classroom pose significant challenges for educators in delivering personalized attention to each student. The present study posits that collaborative endeavors among teachers, parents, and the school environment are imperative to equip students with the necessary skills to address reading difficulties from an early age.